Effect of infectious disease on paramedic students’ willingness to perform mouth to mouth ventilation at a university - Kim, Jee Hee; Uhm, Tai-Hwan; Park, Sang-Kyu (Edelweiss Applied Science and Technology, 2025)
This study was conducted to confirm factors that negatively affect mouth-to-mouth ventilation (MMV) by laypersons. An internet non-face-to-face survey was conducted using NAVER Office with 101 respondents out of 157 paramedic students at a university. Whether or not to apply MMV according to the infection status of adults, children, and infants was analyzed through the Chi-Square test for each variable. There was a statistically significant difference between the proportion of willingness to perform MMV for suspected infection adult patients by male and female students (p=.004), for non-infection adult patients by training session (p=.030), for non-infection adult patients by experience in providing CPR (p=.011), for infection child patients by male and female students (p=.011), for suspected infection child patients by male and female students (p=.040), and for infection infant patients by male and female students (p=.011). Concerns over infection had a negative impact on paramedic students’ willingness to perform MMV.